Cinnamic Acid Activity on Complete Blood Count Tests Against Trichlorfon Residues in Mice - Niba, Kh. Mousa; Jabbar, F. Al-maadhidi; Abrar, N. Mohammd; Eman, H. Qatia; Amal, Ab. Halub; Duha, B. Mohammed; Alaa, D. Kadhum; Azhar, S. Abd-alkharem; Mohamed, Ab. Ayyash; Ishrak, Ab. Ahmed (Journal of Madenat Alelem University College, 2013)
The current study aimed to evaluate the role of cinnamic acid and its activity on complete blood count (RBC, WBC, HG, HCV, MCH, MCHC and Platelets) and protective effect against the trichlorfon which is a chemical compound that damage hepatic cells and has mutagenic effects. Two concentrations of pure cinnamic acid (30 & 60 mg ⁄ kg) were used in the first step to choice the perfect concentration in comparison with negative and positive controls of trichlorfon. The comparison group represent vitamin C. The second step was carried out to understand cinnamic acid mechanism activity towards trichlorfon by used pre- trichlorfon and post – trichlorfon in interaction with perfect concentration of cinnamic acid dose (30 mg ⁄ kg).The analysis showed that cinnamic acid removed kinds of anemia ,leukemia,bone marrow failure, hypoxia, cancer chemotherapy, hemolytic anemia and hormone erythropoietin from kidney failure in post-trichlorfon than pre-trichlorfon perfectly. Therefore, cinnamic acid has cure ability and removed trichlorfon damage and it can be given to patient whom used trichlorfon in transplanting body part surgeries to a void refused the part for 6 days after transplanting surgeries.